EFEITO DE FONTES E DOSES DE FÓSFORO SOBRE A PRODUÇÃO DE FORRAGEM DE Andropogon gayanus CV. PLANALTINA - Costa, Newton de Lucena; Paulino, Valdinei Tadeu; Cardelli, Márcia Atauri; Rodrigues, Antonio Neri Azevedo; Oliveira, José Ribamar da Cruz (REVISTA DE AGRICULTURA, 2015)
EFEITO DE FONTES E DOSES DE FÓSFORO SOBRE A PRODUÇÃO DE FORRAGEM DE Andropogon gayanus CV. PLANALTINA